A ABUSIVIDADE DA DISPONIBILIZAÇÃO DE CARDÁPIOS EXCLUSIVAMENTE DIGITAIS VIA QR CODE EM BARES, RESTAURANTES E CONGÊNERES - ROCHA, ALINE XAVIER RAMOS (2025)
This paper aims to analyze the increasingly common practice of exclusively providing digital menus via QR code in bars, restaurants, and similar establishments. Although it initially emerged as a sanitary measure during the COVID-19 pandemic, this practice has persisted beyond the pandemic period, raising questions regarding its compatibility with consumers’ basic rights. The research is grounded in a critical analysis of current legislation, particularly the Federal Constitution of 1988 and the Consumer Defense Code, considering fundamental principles such as objective good faith, the presumed vulnerability of the consumer, the duty of clear information, and the right to freedom of choice. The study begins with the observation that the replacement of physical menus with digital ones, while offering logistical and economic advantages for suppliers, creates significant access barriers for certain social groups, including the elderly, people with disabilities, and individuals facing digital exclusion. This restriction undermines the full exercise of private autonomy and access to basic information about products and services. Furthermore, requiring the use of mobile devices and internet connectivity to access essential information may constitute a violation of the principle of human dignity by excluding portions of the population from the full exercise of their rights. In this regard, the research concludes that the imposition of exclusively digital menus, without providing accessible alternatives, may constitute an abusive commercial practice, as it disproportionately limits access to information and the consumer's right to choose. Therefore, it is essential to strike a balance between technological innovation and the effective protection of fundamental rights in consumer relations, highlighting the importance of state intervention and the implementation of measures that promote inclusion and accessibility.